The Effect of Digital Marketing and Influencers on Purchasing Decisions for SMEs Culinary Products Spaghetti Tulang Lampung - Rizky, Alivia; Asnusa, Soraya (Proceeding International Conference on Information Technology and Business, 2023)
Technological advancements and the development of social media have changed the marketing landscape, especially for Micro, Small and Medium Enterprises (SMEs). The purpose of this study is to explore the effect of digital marketing and the role of influencers in influencing purchasing decisions for SMEs products